Exploring how Grade 11 chemistry teachers make use of the periodic table of elements when mediating learning of writing and balancing chemical equations - Kambeyo, Reginald Ndeshipanda (Rhodes University, Faculty of Education, Department of Education)
The periodic table of elements is central to the study of chemistry and other disciplines of science, yet Namibian learners do not perform satisfactorily in topics which require its use in answering questions. The purpose of this study, therefore, was to explore how Grade 11 chemistry teachers make use of the periodic table of elements to mediate the learning of writing and balancing chemical equations. The study was carried out with two chemistry teachers in two rural schools in the northern part of Namibia. It was underpinned by an interpretive paradigm, within which a qualitative case study approach was employed. Data were collected through in-depth interviews (semi-structured and stimulated recall interviews), observations, and participants' group reflections. The latter afforded the participants and myself room to reflect and share ideas at the end of the data gathering process. I used Shulman's Pedagogical Content Knowledge as my theoretical framework in this study and the data sets were analysed using the five Topic-Specific Pedagogical Content Knowledge (TSPCK) components adapted from Mavhunga and Rollnick. The findings revealed that teachers demonstrated positive attitudes towards the use of the periodic table of elements when teaching the writing and balancing of chemical equations. However, challenges regarding inadequate materials that hindered the teaching and learning process were observed. Another finding of this study was that teachers used a variety of mediation tools such as prior knowledge and appropriate representations to enhance learning. However, during lesson observations, the findings revealed that there was an imbalance in the knowledge of using easily accessible resources as opposed to what teachers had indicated during the semi-structured interviews. Nonetheless, teachers' group reflections influenced them to analyse and improve their lessons. The study thus recommends that there is a need for continuing professional development for chemistry teachers so that teachers can be afforded opportunities and spaces to share subject matter knowledge, pedagogical content knowledge as well as easily accessible resources that they can use to enhance teaching of chemistry in their classrooms.
Keywords: Chemistry-- Study and teaching (Secondary)-- Namibia; Periodic table of the elements; Chemical equations-- Study and teaching (Secondary)-- Namibia; Chemistry teachers Attitudes-- Namibia; Pedagogical content knowledge; Topic-Specific Pedagogical Content Knowledge (TSPCK)